The Digital Transformation of the Public Sphere
XXI, 433 p. 7 illus., 6 illus. in color.
Keywords: ‘People are on the move, and so is technology. In this turbulent account of a breathtaking global range, we discover a treasure trove of bottom-up case studies on community-based social media use. Using the lens of migration we get a unique insight into diaspora networks and the rise of conflicts in the digital realm. The collected stories prove that the public sphere is no longer a given and is being rebuilt as we speak on the net.’ Geert Lovink, Institute of Network Cultures, the Netherlands ‘Through a series of diverse and intriguing cross disciplinary case studies of digital activism set against the background of migration and austerity this vibrant collection of essays problematises the idea of the digital public sphere. What emerges is a demonstration of the nuances of digital activism and the range of disciplinary theoretical resources implicated in the study of the digital public sphere.’ Peter Lunt, University of Leicester, UK ‘With breathtaking conceptual and geographical scope, this volume explodes our notion of digital politics. In its comprehensive approach to studying technology as narratives, users and infrastructures in crisis and conflict situations, this carefully curated book provokes lively dialogue about risks and opportunities of our contemporary public sphere’ Jonathan Ong, University of Leicester, UK Bringing together contributions from the fields of sociology, media and cultural studies, arts, politics, science and technology studies, political communication theory and popular culture studies, this volume engages both with theoretical debates and detailed empirical studies, showcasing how the public sphere is transformed by digital media, and in turn how this digital public sphere shapes and is shaped by debates surrounding crisis, conflict, migration and culture. Case studies from Bulgaria, Nigeria, China, Greece, Italy, Cyprus, UK, Mexico and India are discussed in detail.